A Microfabrication Technique for High-Performance Diffractive Optical Elements Tailored for Numerical Simulation - Xingang Dai; Yanjun Hu; Bowen Niu; Qun Dai; Yu Ao; Hongru Zhang; Gaoshan Jing; Yuan Li; Guofang Fan (Nanomaterials)
Diffractive optical elements (DOEs) are specialized optical components that manipulate light through diffraction for various applications, including holography, spectroscopy, augmented reality (AR) and virtual reality (VR), and light detection and ranging (LiDAR). The performance of DOEs is highly determined by fabricated materials and fabrication methods, in addition to the numerical simulation design. This paper presents a microfabrication technique optimized for DOEs, enabling precise control of critical parameters, such as refractive index (RI) and thickness. Using photolithography, we fabricated high-precision photoresist patterns on silicon and sapphire substrates, with 3 × 3 and 3 × 5 DOE beam splitter as examples. The results show a strong match between simulation and experimental data, with discrepancies of just 0.53% and 0.57% for DOE on silicon and sapphire substrates, respectively. This approach offers potential for advancing high-performance DOE devices in semiconductor manufacturing, supporting next-generation optical systems.